2016
DOI: 10.1680/jgeot.15.p.205
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave velocity and stiffness of sand: the role of non-plastic fines

Abstract: Current knowledge on the shear wave velocity (V s ) and associated stiffness (G 0 ) of sand is built mainly on the results of extensive laboratory studies on clean quartz sands. Often natural sands are not clean, but contain a certain amount of fines. The role of fines in altering the stiffness of sands is a matter of great concern, yet remains poorly understood. This paper presents an investigation into the problem through well-controlled laboratory experiments in conjunction with analysis and interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(36 citation statements)
references
References 51 publications
6
30
0
Order By: Relevance
“…The ratio of the median particle diameters (D50) of the coarse and fine particles (χ) and the fines context (Fc = mass of fines/total mass) both determine the behaviour [4]. Yang & Liu [5] used mixtures of Toyoura sand and crushed silica fine (χ ≈ 4) and found that G0 dyn decreases as Fc increases up to 30%. They prepared the mixtures maintaining an equivalent range of global void ratios (e).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the median particle diameters (D50) of the coarse and fine particles (χ) and the fines context (Fc = mass of fines/total mass) both determine the behaviour [4]. Yang & Liu [5] used mixtures of Toyoura sand and crushed silica fine (χ ≈ 4) and found that G0 dyn decreases as Fc increases up to 30%. They prepared the mixtures maintaining an equivalent range of global void ratios (e).…”
Section: Introductionmentioning
confidence: 99%
“…The general procedure of the 1-D compression test followed the British Standard (BS 1377) [24]. In contrast, as there are no specified procedures for the resonant column test, we performed the test in accordance with the way prescribed in the literature [25,26]. In the compression test, a modified oedometric compaction cell was use, i.e., a 27.6 mm diameter cell that is 30 mm high, which can apply a maximum vertical load of 16 MPa (Figure 2a).…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…Note that the strain level involved in the resonant column test was in the order of 10 −5 or below; accordingly, the small strain shear modulus (G0) of the specimen was determined. Those interested in more detailed information can refer to Yang and Liu [26] and Liu et al [27] for more features about the resonant column technique. Figure 3 presents the results obtained for the rubber-sieved calcareous sand mixtures of different rubber contents and initial void ratios.…”
Section: Sample Preparation and Test Methodsmentioning
confidence: 99%
“…For comparison, Fig. 26 here presents the variation of parameter 1·2 0·8 Iruma sand (Iwasaki & Tatsuoka, 1977) Yunlin sand (Chien & Oh, 1998) Ottawa sand (Salgado et al, 2000) Toyoura sand, BE (Yang & Liu, 2016) Toyoura sand, RC (Yang & Liu, 2016) …”
Section: Authors' Replymentioning
confidence: 99%
“…Exponential relation between A and f c The authors (Yang & Liu, 2016), by using c = 2·17 for Toyoura sand (sub-round) with crushed silica fines in the empirical equation of Hardin and Black (1966), suggested that A deceases with increasing f c and can be presented by a simple exponential function of f c (their equation (4)). However, the A-f c relationship for a specific sand-fines mixture may not be applicable to another sand-fines mixture, as evident from the database of Rahman et al (2012) and presented as Fig.…”
mentioning
confidence: 99%